Handbook of research on the platform economy and the evolution of e-commerce - Ertz, Myriam (Advances in electronic commerce series., 2022)
"This book provides relevant theoretical frameworks and the latest empirical research findings in the areas of e-commerce and the collaborative economy or sharing economy, offering a comprehensive perspective on the platform economy by connecting both the e-commerce and the collaborative economy research streams together"--